2023
DOI: 10.1126/scisignal.adg0661
|View full text |Cite
|
Sign up to set email alerts
|

Convergent activation of Ca 2+ permeability in two-pore channel 2 through distinct molecular routes

Ryo Saito,
Qianru Mu,
Yu Yuan
et al.

Abstract: TPC2 is a pathophysiologically relevant lysosomal ion channel that is activated directly by the phosphoinositide PI(3,5)P 2 and indirectly by the calcium ion (Ca 2+ )–mobilizing molecule NAADP through accessory proteins that associate with the channel. TPC2 toggles between PI(3,5)P 2 -induced, sodium ion (Na + )–selective and NAADP-induced, Ca 2+ –permeable states in response to these cues. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…We show that activation of TRPML1 with ML-SA1/PI(3,5)P 2 and TPCs with NAADP produces luminal responses, but the latter were not consistent. Recent studies have shown that NAADP binds to soluble binding proteins to activate TPCs (Gunaratne et al, 2023;Saito et al, 2023). It is possible that loss of these proteins upon permeabilization may account for NAADP insensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…We show that activation of TRPML1 with ML-SA1/PI(3,5)P 2 and TPCs with NAADP produces luminal responses, but the latter were not consistent. Recent studies have shown that NAADP binds to soluble binding proteins to activate TPCs (Gunaratne et al, 2023;Saito et al, 2023). It is possible that loss of these proteins upon permeabilization may account for NAADP insensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on the NAADP regulation of TPCs has shown that NAADP likely does not directly bind to the TPCs but via binding proteins such as Lsm12 [23] . [24] So far, the selectivity and ligand-gating mechanisms of hTPC2 are insufficiently understood. The selectivity filter (SF) sequences of hTPC2 are 271TAN273 (filter I) and 652VNN654 (filter II) [25] .…”
Section: Introductionmentioning
confidence: 99%
“…NAADP is a potent and well-known Ca 2+ -mobilizing second messenger, which initiates Ca 2+ release from endo-lysosomal organelles [19] . Recent research on the NAADP regulation of TPCs has shown that NAADP likely does not directly bind to the TPCs but via binding proteins such as Lsm12 [26][18,27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation